Preservation of culture in Royal Klang Town / Ireina Izwan and Dr. Mohd Azren Hassan - Izwan, Ireina; Hassan, Mohd Azren (College of Built Environment, 2023)
Royal Klang Town is known as one of the oldest town in Malaysia rich with history, tradition and customs.